2018
DOI: 10.1007/s00467-018-4117-x
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of hematocrit correction on evaluation of tacrolimus target exposure in pediatric kidney transplant patients

Abstract: BackgroundTacrolimus is an important immunosuppressive agent with high intra- and inter-individual pharmacokinetic variability and a narrow therapeutic index. As tacrolimus extensively accumulates in erythrocytes, hematocrit is a key factor in the interpretation of tacrolimus whole blood concentrations. However, as hematocrit values in pediatric kidney transplant patients are highly variable after kidney transplantation, translating whole blood concentration targets without taking hematocrit into consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…This vulnerability to hemolysis makes analyses of plasma tacrolimus concentrations as a routine practice a major challenge. Our results concur with previous studies that suggest hematocritcorrected whole-blood concentrations could be of use for improved target exposure [11,24,33]. We assume that only correction to hematocrit is sufficient while protein levels will not have a large effect on the whole-blood concentrations because the majority of tacrolimus was associated with erythrocytes and plasma concentrations were < 1% of the whole-blood concentrations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This vulnerability to hemolysis makes analyses of plasma tacrolimus concentrations as a routine practice a major challenge. Our results concur with previous studies that suggest hematocritcorrected whole-blood concentrations could be of use for improved target exposure [11,24,33]. We assume that only correction to hematocrit is sufficient while protein levels will not have a large effect on the whole-blood concentrations because the majority of tacrolimus was associated with erythrocytes and plasma concentrations were < 1% of the whole-blood concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…Tacrolimus extensively binds to red blood cells and blood proteins. As a consequence, tacrolimus whole-blood distribution is strongly affected by hematocrit and protein concentrations, e.g., albumin, lipoproteins, and α 1 -acid glycoprotein [7][8][9][10][11]. While wholeblood concentrations are commonly used for therapeutic drug monitoring, the unbound tacrolimus plasma concentrations might be better related to the toxicity and efficacy of tacrolimus [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Hematocrit was analyzed as covariate on CL and/or V1 based on literature. [26,27] Recipient and donor CYP3A4*22 and CYP3A5*3 genotype were analyzed on CL and F in an univariate analysis. In addition, using automated scm, donor, recipient and combined CYP3A4*22 and CYP3A5*3 genotype , together with IL-6, -10 and-18 genotype were analyzed on CL.…”
Section: Covariatesmentioning
confidence: 99%
“…Because of the large influence of hematocrit on wholeblood concentrations, hematocrit-corrected whole-blood concentrations may be suitable as a substitute for the prediction of clinical outcomes. Two studies showed that for clinically stable renal transplants, hematocrit standardized whole-blood concentrations improved the prediction of whole-blood concentrations [18,47]. Størset assumed that when hematocrit increases, the unbound concentration remains similar, which may be an incorrect assumption in patients with lower hematocrit fractions [18].…”
Section: Hematocrit-corrected Tacrolimus Dosingmentioning
confidence: 99%